2021
DOI: 10.1186/s40249-021-00908-2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of severe dengue: a systematic review and meta-analysis

Abstract: Background Severe dengue is a life-threatening complication; rapid identification of these cases, followed by adequate management is crucial to improve the clinical prognosis. Therefore, this study aimed to identify risk factors and predictors of severe dengue. Methods A literature search for studies reporting risk factors of severe dengue among individuals with dengue virus infection was conducted in PubMed, Scopus and Web of Science database fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
53
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 50 publications
6
53
1
6
Order By: Relevance
“…[38][39][40] Many previous studies also showed that among patients with severe dengue infection, up to 55.9% suffered from a concurrent bacterial infection. 23,26 Dengue infection might also lead to serious morbidities such as dengue syndrome and dengue haemorrhagic fever, [41][42][43][44][45][46] contributing to the estimated high rates of mortality and ICU admissions in the current study.…”
Section: Discussionmentioning
confidence: 81%
“…[38][39][40] Many previous studies also showed that among patients with severe dengue infection, up to 55.9% suffered from a concurrent bacterial infection. 23,26 Dengue infection might also lead to serious morbidities such as dengue syndrome and dengue haemorrhagic fever, [41][42][43][44][45][46] contributing to the estimated high rates of mortality and ICU admissions in the current study.…”
Section: Discussionmentioning
confidence: 81%
“…Adults are more likely to develop severe bleeding, and this may be more difficult to manage than plasma leakage, for which judicious fluid replacement is often effective [3, 6, 8, 17, 23, 24, 46]. Comorbid illness, including poorly-controlled diabetes mellitus (hemoglobin A1c >7%) and renal disease, have been associated with SD [16, 18], and hypertension has also been identified in certain studies [18]. A gender difference among clinically severe dengue has varied across studies [1, 6, 13, 17, 18].…”
Section: Discussionmentioning
confidence: 99%
“…Comorbid illness, including poorly-controlled diabetes mellitus (hemoglobin A1c >7%) and renal disease, have been associated with SD [16, 18], and hypertension has also been identified in certain studies [18]. A gender difference among clinically severe dengue has varied across studies [1, 6, 13, 17, 18]. In our population, 66.4% of DWS-/DWS+ cases were female in comparison to only 26.1% of SD cases, and this difference remained significant after controlling for age and comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, currently more severe forms of dengue (DHF/DSS) are predominantly seen in the older population in some countries, where CFRs tend to be higher than in younger individuals [ 79 , 83 ]. However, some studies have shown that CFRs are higher in children, and these differences possibly reflect the differences in disease epidemiology in different countries [ 119 ]. Men were significantly more likely to have severe illness in COVID-19, whereas no such associations have been seen with dengue [ 39 , 60 ].…”
Section: Introductionmentioning
confidence: 99%